Paracentesis-induced acute kidney injury in decompensated cirrhosis – prevalence and predictors - Patil, Vaibhav (Clin Exp Hepatol, 2019)
AIM OF THE STUDY: A subgroup of cirrhotic patients undergoing therapeutic paracentesis develop acute kidney injury (AKI) despite adequate colloidal replacement. The aim of the study was to determine the prevalence and predictors of paracentesis-induced AKI in cirrhotic patients with normal baseline renal parameters and adequate colloidal replacement. MATERIAL AND METHODS: This prospective, observational analytical study was undertaken between April 2015 and April 2017. All patients undergoing therapeutic paracentesis were enrolled as per inclusion and exclusion criteria. Based on Acute Kidney Injury Network (AKIN) criteria for AKI, comparative analysis was performed between those developing and not developing AKI for demography, renal parameters, frequency and quantity of paracentesis per session. Univariate and multivariate regression analyses were performed to determine the predictors of AKI. RESULTS: Altogether, 177 patients underwent 859 therapeutic paracenteses. Ninety-four paracentesis sessions resulted in an AKI (10.9%). The median number of paracenteses was 10 (range 1-25) and the median volume of fluid drained per paracentesis was 6 l (1-20 l). In univariate analysis, younger age (p < 0.02), higher MELD (Model For End-Stage Liver Disease) score (p < 0.0001), CTP (Child-Turcotte-Pugh) class C (p < 0.017) and prior history of renal dysfunction (p < 0.0001) were significantly associated with AKI. For each liter of fluid drained, the risk of AKI increased by 1.24 times. Frequency of paracentesis did not influence the AKI. In multivariate logistic regression, the significant predictors of AKI were past renal dysfunction, a higher MELD and volume of fluid tapped at paracentesis. CONCLUSIONS: Post-paracentesis AKI occurs in 10.9% of cases, despite adequate colloid replacement. For each 1 l of fluid drained during paracentesis, the risk of AKI increased by 1.24 times.